Complex karyotype in a polycythemia vera patient with a novel SETD1B/GTF2H3 fusion gene. Issue 4 (April 2014) - Tiziana Storlazzi, Clelia; Pieri, Lisa; Paoli, Chiara; Daniele, Giulia; Lasho, Terra; Tefferi, Ayalew; Vannucchi, Alessandro M.
<x xml:space="preserve">Abstract</x> The patient had been diagnosed with polycythemia vera (PV) in 1999, at the age of 61, according to the criteria of the Polycythemia Vera Study Group (PVSG) on the basis of the increased red cell mass by isotope determination, normal oxygen saturation, low plasma erythropoietin level, presence of endogenous erythroid colonies (EEC), and splenomegaly. Histopathology of bone marrow biopsy was also consistent with polycythemia vera with no evidence of increased reticulin fibrosis. A karyotype analysis was not performed at that time. He had been treated initially with phlebotomies and then with hydroxyurea with the aim to obtain a better control of hematocrit; he was under low‐dose aspirin. In 2009, 10 years after the diagnosis, while the patient was still being treated with hydroxyurea and phlebotomies, he noticed worsening of general conditions and fatigue, and the appearance of night sweats; he also reported that his spleen volume had increased rapidly in the past few months. He complained of severe pruritus especially after (but not limited to) a shower. He was referred to our center for further evaluation. At presentation, his blood counts were as follows: hemoglobin 157 g/L, hematocrit 54.7%, leukocytes 13.1 × 109/L, platelets 238 × 109/L, LDH 856 U/L (normal upper limit, 250 U/L). Blood film examination showed neutrophilia (8.9 × 109/L) but immature myeloid cells and nucleated erythroblasts were absent. The spleen was 14 cm below the left costal margin, the liver was at 4 cm below the right costal margin. He was found to harbor the JAK2V617F mutation with an allele burden of 85% and the circulating CD34+ cell count was 14 × 106/L. A bone marrow biopsy showed the presence of hyperplasia of myeloid and erythroid lineages, increased number of scattered megakarocytes without overt morphologic abnormalities; reticulin fibrosis was grade 1 according to the European classification. On these basis, we considered the patient as presenting the features of PV according to the 2008 WHO classification of myeloid neoplasms associated with grade 1 reticulin fibrosis. Am. J. Hematol. 89:438–442, 2014. © 2014 Wiley Periodicals, Inc.